Poly(ethylene oxide) and its blends with sodium alginate - EROĞLU, MEHMET SAYIP (ELSEVIER SCI LTD, 2005)
A series of blends based on poly(ethylene oxide) (PEO) and sodium alginate (NaAlg) were prepared by solution casting method. The blends thus obtained were characterized by using Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), tensile strength test, contact angle measurements and atomic force microscopy (AFM). FT-IR studies indicate that there are the hydrogen bonding interactions due to the ether oxygen of PEO and the hydroxyl groups of NaAlg. The thermal stability of the blends was slightly affected with increasing NaAlg content. DSC results showed that both melting point and crystallinity depend on the composition of the blends. Mechanical properties of the blend films were improved compared to those of homopolymers. Surface free energy components of the blend films were calculated from contact angle data of various liquids by using Van Oss-Good methodology. It was found that the surfaces both of the blends are enriched in low surface free energy component, i.e. NaAlg. This conclusion was further confirmed by the AFM images observation of the surface morphology of these blends. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: miscibility; poly(ethylene oxide); sodium alginate; FT-IR; PHYSICAL-PROPERTIES; POLYETHYLENE OXIDE; POLYMER BLENDS; COPOLYMER; CHLORIDE); DELIVERY; SURFACES